2015
DOI: 10.1002/jhbp.223
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic fistulae secondary to trypsinogen activation by Pseudomonas aeruginosa infection after pancreatoduodenectomy

Abstract: Infection with P. aeruginosa perioperatively to PD entails secretion of a protease activator of trypsinogen to trypsin. Bacterial infection control in the perioperative PD period could be crucial to prevent development of pancreatic fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Previous studies found that Enterococcus, Pseudomonas, and Candida were associated with POPF after PD [9,10,48]. Due to the small sample size of these studies, fewer other bacteria were isolated.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies found that Enterococcus, Pseudomonas, and Candida were associated with POPF after PD [9,10,48]. Due to the small sample size of these studies, fewer other bacteria were isolated.…”
Section: Discussionmentioning
confidence: 90%
“…However, a clinical study in patients who underwent resection and developed postoperative pancreatic fistulae (POPF) found that Pseudomonas aeruginosa and Enterobacter cloacae isolated from drainage fluid in patients with clinically relevant (grade B/C) POPF could cause trypsinogen activation. 70 The investigators further found that trypsinogen activation by P. aeruginosa and E. cloacae were preventable by the use of a serine protease inhibitor in vitro and that a protease in the supernatant from P. aeruginosa-positive cultures acted as the trypsinogen activator. 70 Again, this is extrapolation from data from a different setting, but serves to show that certain bacteria have the ability to activate trypsinogen into trypsin and thereby eliciting effects that may have clinical relevance (Figs.…”
Section: Why Has Trypsin Yet To Be Investigated As a Major Player Befmentioning
confidence: 99%
“…70 The investigators further found that trypsinogen activation by P. aeruginosa and E. cloacae were preventable by the use of a serine protease inhibitor in vitro and that a protease in the supernatant from P. aeruginosa-positive cultures acted as the trypsinogen activator. 70 Again, this is extrapolation from data from a different setting, but serves to show that certain bacteria have the ability to activate trypsinogen into trypsin and thereby eliciting effects that may have clinical relevance (Figs. 1 and 2).…”
Section: Why Has Trypsin Yet To Be Investigated As a Major Player Befmentioning
confidence: 99%
“…Previous studies have shown that serum presepsin is useful for the early detection of bacterial infection and sepsis (11,12). POPF is considered to be closely associated with bacterial infection (8,14). Indeed, surgical site bacterial infection involves the secretion of certain protease activators in the pancreatic juice that convert trypsinogen to trypsin, subsequently inducing CR-POPF (14).…”
Section: Introductionmentioning
confidence: 99%
“…POPF is considered to be closely associated with bacterial infection (8,14). Indeed, surgical site bacterial infection involves the secretion of certain protease activators in the pancreatic juice that convert trypsinogen to trypsin, subsequently inducing CR-POPF (14). However, no study has focused on the utility of presepsin as a predictive marker for CR-POPF.…”
Section: Introductionmentioning
confidence: 99%